Surface etching evolution of mechanically polished single crystal diamond with subsurface cleavage in microwave hydrogen plasma: Topography, state and electrical properties. (May 2022) - Zheng, Yuting; Jia, Yanwei; Liu, Jinlong; Wei, Junjun; Chen, Liangxian; An, Kang; Yan, Xiongbo; Zhang, Xiaotong; Ye, Haitao; Ouyang, Xiaoping; Li, Chengming
Abstract: Surface etching of single-crystal diamond (SCD) in hydrogen plasma plays a decisive role for high-quality homoepitaxy and surface conduction of diamond. The complexity of surface/subsurface condition such as defects would give rise to the distinct morphology features and even further result in the unpredictable properties. Correspondingly, the evolutionary relationship between the morphology and electrical properties of mechanically polished SCDs which have typical cleavage damage in microns depth after hydrogen plasma treatment still needs to be further completed. In this work, the chemical vapor deposited (CVD) SCDs with uniform polishing-caused subsurface cleavage were immersed in microwave hydrogen plasma for variable duration. Time-dependent morphological evolution, multi-mode etched pits (EPs) (resulting from local defects/cracks and dislocations) and associated etching mechanism were comprehensively studied. At the early stage of plasma treatment before 60 min, owing to the obvious surface roughing generated by preferential etching (with the rate of >400 nm/h) of severe mechanically damaged regions, the hole mobility was significantly deteriorated, also accompanying with the apparent drop of sheet concentration. Concurrently, the deposited surface sp 2 amorphous carbon ( a -C) nanodots on diamond surface and non- sp 3 hydrogen bonds reconstruction, which arising from defect-etching produced local abundant carbon-containing radicals or possible exfoliation generated by hydrogen penetration of massive defective regions, also would play an adverse role for the conduction associated with (100) C–H surface. However, the surface roughness was reduced from the maximum 13.2 nm–4.2 nm by prolonging etching, resulting from the smoothing effect of small-angle crystal misorientation on waved height difference related to the uniform (111) cleavage and the removal of dense irregular EPs associated with polishing-induced local defects as well as the vanishing of surface a -C nanodots. In this case, the improvement of surface electrical properties together with the negative correlation of the mobility and sheet concentration were appeared by the gradual formation of (100) diamond surface and the building of uniform (100) C–H bonds. Highlights: CVD SCDs with typical subsurface damages(defects) were treated in pure hydrogen plasma. Morphology evolution associated with polishing defects was time-dependently presented. Surface sp 2 nanodots deposition from defect-etching and CH reconstruction would affect electrical properties.